Forms of Mothers' Political Communication Participation in Improving Women's Political Roles in the 2019 Presidential Election in Medan City - Evi Sakdiah; Hasrat Efendi Samosir; Zainun Zainun; Anang Anas Azhar (Budapest International Research and Critics University, 2021)
The participation of women's political communication who was present in the 2019 presidential election was not just jargon and selling politics. But it must be realized that the presence of mothers in Indonesian politics has been able to encourage an increase in women's participation in the 2019 Election. Especially voters in Medan City. The level of women's political participation has increased when compared to the previous elections that have taken place. This increase in voters actually raises the question of why the number of voters in the city of Medan has increased? Is there any influence of mothers participating in the 2019 presidential election? The democratic party for the simultaneous presidential and vice-presidential elections as well as the legislative elections on 17 April 2019 had just been held. The democratic party took place quite safely and smoothly with a quite encouraging level of participation. For the City of Medan, the participation rate was quite high, namely 74.20% for the Presidential and Vice-Presidential Election and 73.67% for the Medan City DPRD Election. This data shows that there was a sharp increase in the participation rate from the 2014 Presidential and Vice-Presidential and Legislative Elections, although it still has not reached the national target set at 77.5%.